The development of a hexaplex-conventional PCR for identification of six animal and plant species in foodstuffs. (1st February 2016) - Safdar, Muhammad; Junejo, Yasmeen
Highlights: Hexaplex PCR assays to identify six animal and plant species in a tube. The assays are specific, sensitive and reproducible. The practical approach is much easier, cheaper and faster. Successfully detection of food allergens and low price meats. Abstract: A hexaplex-conventional PCR assay was developed for identification of five meat and one plant species origins in foodstuffs simultaneously. The method merges the use of horse ( Equus caballus ), soybean ( Glycine max ), sheep ( Ovis aries ), poultry ( Meleagris meleagris ), pork ( Sus scrofa ), and cow ( Bos taurus ) specific primers that amplify fragments (horse; 85 bp, soybean; 100 bp, sheep; 119 bp, poultry; 183 bp, pork; 212 bp and cow; 271 bp) of the mitochondrial cyt b, lectin, 12S rRNA, 12S rRNA, ATPase subunit 6 genes and ATPase subunit 8 genes respectively, and a universal 18S rRNA primers that amplifies a 141 bp. Multiplex analysis of the reference food samples showed that detection limit of the hexaplex assay was 0.01% for each species. Taken together, all data indicated that this hexaplex PCR assay was a simple, fast, sensitive, specific, and cost-effective detection method for horse, soybean, sheep, poultry, pork and cow species in foodstuffs.